Deep Venous Thrombosis (DVT) risk assessment on routine hemodialysis patient using Padua prediction score - Benny Tjan; I Gusti Ngurah Agung Tresna Erawan; Yenny Kandarini (Indonesian Vascular Access Association (IVAA), 2021)
Introduction: Hemodialysis requires invasive vascular access (VA) procedure which could emerge deep venous thrombosis (DVT) complication. Apart from VA, other risk factors, either modifiable or unmodifiable, could increase DVT risk. Those factors can be assessed by Padua Prediction Score (PPS). This study aims to assess which risk factors in PPS increase the risk of developing DVT in routine hemodialysis patients at BHCC main clinic. Methods: This research is a descriptive observational study with simple random sampling. The participants were 58 routine hemodialysis patients in BHCC. The inclusion criteria of this study were the ages above 17 years old, had history hemodialysis more than one, the patient willing to become of the sample subject. The patient that incompletely fulfills the questionnaire were already treated with anticoagulation were admitted for VTE, and had a history of discontinuing hemodialysis were excluded. The data were gathered using a questionnaire according to PPS. The data was analyzed by using SPP 25.0. The descriptive data was provided in a table and pie chart. Results: Based on the results of the PPS, 11 patients (18.96%) were among the high risk, and 47 patients (81.04%) were at low risk. The most potent risk factor in increasing the risk of DVT is reduced mobility with a risk priority number (RPN) of 30 (severity=3, occurrence=10). Recent (≤one month) trauma and surgery entail on second with an RPN of 24 (severity=2, occurrence=12). The third is occupied by heart and/or respiratory failure with a RPN of 14 (severity=1, occurrence=14). Previous VTE history with a RPN of 12 (severity=3, occurrence=4) placed fourth, followed by age≥ 70 (RPN=8, severity=1, occurrence=8) and obesity (BMI>= 30) with a RPN of 4 (severity=1, occurrence=4) at fifth and sixth respectively. Conclusion: